THE INFLUENCE OF THE OPENING ANGLE OF THE SOIL PUSHER OF THE COMBINED MACHINE LEVELER ON ITS PERFORMANCE - Sharipov Shuhrat Pо‘latovich (Journal of Artificial Intelligence and Digital Economy, 2024)
The article presents the results of experimental research on the influence of the opening angle of the soil pusher of the combined machine leveler used in the preparation of land for planting on the performance indicators of the leveler.